RANCANG BANGUN SISTEM INFORMASI PERSEDIAAN IKAN PADA CV. ZOOBAIR WIMA - Rifqi Syafar, - (2018)
This research is done to make the design of fish preparation information system at CV. Zoobair Wima. In the process of recording fish preparation is still done manually. The purpose of this research is information system of fish preparation information on CV. Zoobair Wima to facilitate the work of administrative staff in managing data Preparing fish The process of inputting and checking data Preparing fish can be faster, precise and efficient. The method used for this research is waterfall. Data were analyzed using PIECES method (Perfomance, Information, Economics, Efficiency, Services). While the application design method UML (Unified Modeling Languange) and information systems designed by the author, using PHP (Personal Home Page) as a programming language, MySQL as a database server